Efficacy and Safety of Direct Oral Anticoagulants for Secondary Prevention of Cancer-Associated Thrombosis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Prospective Cohort Studies - Wang, Yunsong; Lv, Haichen; Li, Daobo; Chen, Cheng; Gu, Guangming; Sun, Yang; Yang, Xiaolei; Liu, Ying; Fang, Fengqi; Liu, Jiwei; Tse, Gary; Xia, Yunlong (Frontiers in Pharmacology, 2019)
Background: Venous thromboembolism (VTE) is a common complication in patients with cancer. Direct oral anticoagulants (DOACs) have been proved to be effective on anticoagulation therapy in many diseases. However, the efficacy and the safety of DOACs in the secondary prevention of cancer-associated thrombosis (CAT) remain unclear. To assess the value of DOACs in patients with CAT, we performed a systematic review and meta-analysis of randomized controlled trials (RCTs) and prospective cohort studies. Methods: Medline, EMBASE and the Cochrane Library were searched from their earliest date through to June 2018. Two investigators independently assessed eligibility. Data were extracted by one investigator and verified by the second investigator. The efficacy outcome of this study was recurrent VTE, whereas the safety outcome was major and clinically relevant non-major bleeding. Relative risks (RRs) and their corresponding 95% confidence interval (CI) were determined. To pooled the results, the Mantel-Haenszel fixed-effects or random-effects models were used. Results: A total of nine articles (six RCTs and three prospective studies) involving 2697 patients with CAT who were prescribed DOACs (Apixaban, Edoxaban, Rivaroxaban or Dabigatran) and 2852 patients who were prescribed traditional anticoagulants (VKAs, LMWH, Dalteparin, Enoxaparin) were compared. VTE recurrence in the DOAC group was significantly lower than that observed in the traditional anticoagulant group (RR: 0.60; 95%CI: 0.49–0.75; I2: 0%; p <0.00001). No significant difference in bleeding risk between both groups was found (RR:0.95; 95%CI: 0.67–1.36; I2: 75%; p=0.79). Conclusions: Our findings showed that anticoagulant therapy with DOACs may be more effective than traditional anticoagulants to prevent recurrent VTE in patients with CAT, while the safety of DOACs may be equal to that of traditional anticoagulants. These findings support the use of DOACs as the first-line therapy for secondary prevention of CAT in most cancer patients.